Read My Lips? Taxes and Elections - Clemens Fuest; Klaus Gründler; Niklas Potrafke; Fabian Ruthardt; Fabian Ruthardt (Center for Economic Studies and ifo Institute (CESifo), 2021)
We introduce a new dataset that includes quantitative harmonized indices of tax reforms based on qualitative information of about 900 Economic Surveys from the OECD and 37,000 tax-related news from the IBFD archives. The data set provides indicators on tax reforms for tax rates and tax bases, along with detailed sub-indices for six types of taxes (23 countries, 1960–2014). Relating tax reforms to the timing of elections, we examine electoral cycles in tax reforms. Our results show that politicians postpone tax rate increases to after elections. A key innovation of our data set is the coverage of harmonized indices for six tax types. Examining heterogeneity across tax types, we find that electoral cycles are particularly pronounced for value added tax rates and personal income tax rates.
Keywords: D72; H20; H25; C23; 330; tax reforms; tax systems; tax rates; tax bases; data set; electoral cycles